Reading and writing files - Dennison, Justin; Spurgin, Aubri (Packt Publishing, 2024)
This meticulously crafted course offers an in-depth exploration of Python's file handling capabilities. Beginning with an overview, learners are introduced to the essential concepts of reading and writing files, setting a solid foundation for the subsequent lessons. Each episode, guided by the expert duo Justin and Aubri, builds upon the previous one, ensuring a coherent and progressive learning experience. The course starts by teaching how to open and close files using Python's various modes, moving on to reading file contents with different methods to suit various needs. Writing data to files is covered next, with a focus on practical examples and common pitfalls. The use of context managers is introduced to automate file management, a crucial skill for efficient programming. Advanced topics such as looping through multiple files and leveraging the fileinput module for streamlined file processing are also explored in detail. By the end of the series, participants will have mastered file handling in Python, equipped with the knowledge to implement these techniques in their own projects confidently. This course is an invaluable resource for anyone looking to enhance their programming toolkit with robust file manipulation skills.
Online resource; title from title details screen (O'Reilly, viewed June 17, 2024)
Keywords: Python (Computer program language); Python (Langage de programmation); Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet